2015
DOI: 10.3109/08958378.2014.996272
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of ozone in healthy subjects with and without deletion of glutathione-S-transferase M1

Abstract: Context Exposure to ozone has acute respiratory effects, but few human clinical studies have evaluated cardiovascular effects. Objective We hypothesized that ozone exposure alters pulmonary and systemic vascular function, and cardiac function, with more pronounced effects in subjects with impaired antioxidant defense from deletion of the glutathione S-transferase M1 gene (GSTM1 null). Methods 24 young, healthy never-smoker subjects (12 GSTM1 null) inhaled filtered air, 100 ppb ozone, and 200 ppb ozone for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Keep in mind, high density of industries (steel, oil, and gas) makes Ahvaz as one of the most important emitters (Rad et al 2014). Breathing groundlevel ozone can trigger a variety of health problems including increased rates of hospital admissions, induction of respiratory symptoms, chest tightness, wheezing, congestion, bronchitis, emphysema, asthma, inflammation of airways, cardiopulmonary disease, and death (Frampton et al 2015;Li et al 2015). Furthermore, ozone induces decrements in pulmonary function, shortness of breath, coughing, and throat irritation; reduces lung function; decreases forced vital capacity; and reduces the maximal inspiratory position (Pride et al 2015;Yang et al 2012;Bell and Dominici 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keep in mind, high density of industries (steel, oil, and gas) makes Ahvaz as one of the most important emitters (Rad et al 2014). Breathing groundlevel ozone can trigger a variety of health problems including increased rates of hospital admissions, induction of respiratory symptoms, chest tightness, wheezing, congestion, bronchitis, emphysema, asthma, inflammation of airways, cardiopulmonary disease, and death (Frampton et al 2015;Li et al 2015). Furthermore, ozone induces decrements in pulmonary function, shortness of breath, coughing, and throat irritation; reduces lung function; decreases forced vital capacity; and reduces the maximal inspiratory position (Pride et al 2015;Yang et al 2012;Bell and Dominici 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations on famous episodes from Meuse Valley in Belgium to London in the UK provided a good cornerstone for generations to come to focus on adverse impacts of air pollution (Geravandi et al 2014;Yang et al 2012;Katsouyanni et al 2009). More coal consumption in power plants along with old technologies in governmental and private sectors have caused high concentration of pollutants which exceeded standards (Di Nardo and Laurenti 2015; Frampton et al 2015;Jane and Fanny 2015). There is a strong relationship between air pollution in megacities and both mortality and morbidity in whole population (Franklin et al 2015; Kampa and Castanas 2008;Kariisa et al 2015;Li et al 2015;Goudarzi et al 2015), in which since 1980 so many epidemiological and environmental studies based on statistical models have reported association between air pollutants and hospitalization, diseases, and even mortalities (Pope et al 2002;Lave and Seskin 2013;Norval et al 2011;PAGE 2003;Zallaghi et al 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…Among these, only an observational study detected a significant positive association between subacute exposure (2 and 5 days prior to sampling; Frampton et al 2012) and circulating TF + EV, whereas the other, interventional studies with a single acute exposure showed at most a trend for a positive association (Frampton et al 2015;Stewart et al 2010). Badrnya, Baumgartner, and Assinger (2014) determined the concentration of TF + EV in plasma of young healthy smokers and nonsmokers and found no significant difference.…”
Section: In Vivo Evidence For Tf + Extracellular Vesiclesmentioning
confidence: 99%
“…A number of studies by one group assessed the influence of PM or ozone (O 3 ) exposure on TF + EV in either healthy individuals (Frampton et al 2015) or type II diabetics (Frampton et al 2012;Stewart et al 2010). Among these, only an observational study detected a significant positive association between subacute exposure (2 and 5 days prior to sampling; Frampton et al 2012) and circulating TF + EV, whereas the other, interventional studies with a single acute exposure showed at most a trend for a positive association (Frampton et al 2015;Stewart et al 2010).…”
Section: In Vivo Evidence For Tf + Extracellular Vesiclesmentioning
confidence: 99%
“…To our knowledge, this is one of very few randomized clinical trials that has recruited and stratified subjects based on genotype (47). In particular, we stratified on the common A1166C polymorphism (rs5186) in the 39-untranslated region of the AGTR1 gene, based on its impact on mRNA stability and subsequent transcription of the AGTR1 receptor.…”
Section: Genetic Variation and Mechanisms Of De Effectsmentioning
confidence: 99%